2018
DOI: 10.1016/j.heliyon.2018.e00677
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of the SUR2A-55 splice variant in mouse heart reduces infract size and promotes protective mitochondrial function

Abstract: ATP-sensitive potassium channels found in both the sarcolemma (sarcKATP) and mitochondria (mitoKATP) of cardiomyocytes are important mediators of cardioprotection during ischemic heart disease. Sulfonylurea receptor isoforms (SUR2), encoded by Abcc9, an ATP-binding cassette family member, form regulatory subunits of the sarcKATP channel and are also thought to regulate mitoKATP channel activity. A short-form splice variant of SUR2 (SUR2A-55) was previously shown to target mitochondria and display diaxoxide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
(68 reference statements)
0
9
1
Order By: Relevance
“…Recent studies showed that CCDC51 pairs with ABCB8 to form a mitochondrial ATP sensitive K + channel [10]. During this same period, we observed that the overexpression of a short (55 kDa) splice variant of the sulfonylurea receptor isoform 2A (SUR2A-55) led to cardio-protection and enhanced mitoK ATP activity at rest [11]. In addition, we found that SUR2A-55 associates with glucose handling proteins and may confer cardio-protection via glucose metabolism [14].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Recent studies showed that CCDC51 pairs with ABCB8 to form a mitochondrial ATP sensitive K + channel [10]. During this same period, we observed that the overexpression of a short (55 kDa) splice variant of the sulfonylurea receptor isoform 2A (SUR2A-55) led to cardio-protection and enhanced mitoK ATP activity at rest [11]. In addition, we found that SUR2A-55 associates with glucose handling proteins and may confer cardio-protection via glucose metabolism [14].…”
Section: Introductionmentioning
confidence: 67%
“…For each experiment, three to six male WT or TG SUR2A−55 mice aged 8-12 weeks were used. TG SUR2A−55 mice were previously generated by overexpression of a SUR2A-55 construct by the αmyosin heavy chain promoter [11].…”
Section: Animal Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Specific deletion of exon 5 of ABCC9 , to ablate expression of both plasma membrane and the mitoSUR2 short form, resulted in neonatal cardiomyopathy, potentially due to failure of the heart to transition normally from fetal to mature myocardial metabolism ( 47 ). Conversely, mice overexpressing the 55 kDa short-form protein had improved recovery from ischemia/reperfusion injury relative to WT hearts ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cell membrane, K ATP channels have been reported to be present in mitochondria, and to be involved in regulation of oxidative phosphorylation, and protection from ischemia-reperfusion injury [31][32][33][34] . Recent studies have suggested that this proposed mitoK ATP may contain Kir1.1 and/or SUR2A-55 [35][36][37][38] , but direct evidence is lacking, and even the constitution of any mitoK ATP remains unclear.…”
Section: Molecular Structure Distribution and Regulation Of K Atpmentioning
confidence: 97%